Professional PHP6 - Lecky-Thompson, Ed (Wrox professional guides, 2009)
Reveals the inside scoop for pushing the limits of how to maximize the feature set of PHP 6. This book helps you learn how to use PHP 6 in the larger scheme of enterprise-class software development. It offers practical examples and information that improves your skills for designing and building large-scale, high-performance platforms using PHP 6.